2014
DOI: 10.1097/sla.0000000000000872
|View full text |Cite
|
Sign up to set email alerts
|

The HYSLAR Trial

Abstract: A moderately restrictive fluid regimen with HYS resulted in a statistically significant 25% reduction in complications when adjusted for age, weight, and pancreatic texture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…Established practices of liberal perioperative fluid administration are being challenged in a variety of gastrointestinal operations, as prospective randomized trials comparing restrictive versus liberal fluid practices have demonstrated improved perioperative outcomes [68,11]. While this evidence has been mounting, there is still controversy as to what type of abdominal operations this may apply to, as well as what types of fluid administrative practices constitute “restrictive”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Established practices of liberal perioperative fluid administration are being challenged in a variety of gastrointestinal operations, as prospective randomized trials comparing restrictive versus liberal fluid practices have demonstrated improved perioperative outcomes [68,11]. While this evidence has been mounting, there is still controversy as to what type of abdominal operations this may apply to, as well as what types of fluid administrative practices constitute “restrictive”.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of prospective randomized trials investigating this have been in the setting of elective colorectal surgery, although recently studies in pancreatic surgery are gaining [68,11]. There have been none in esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have found mixed results; however, few trials have focused purely on pancreatic resection. 20 Our previous retrospective analysis of 1030 patients 25 did not show a difference in the Grade 3 complication rate which prompted the current trial.…”
Section: Discussionmentioning
confidence: 80%
“…This was also addressed more recently in a fluid trial using hypertonic saline in the restricted arm. 20 However, two retrospective reviews of fluid management in patients undergoing pancreatectomy did not demonstrate a clinically significant association between postoperative morbidity and intraoperative fluid administration. 25,26 In an effort to definitively address this question we conducted a prospective randomized trial of Liberal (LIB) versus Restricted (RES) fluid administration for patients undergoing elective pancreatectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation